2009
DOI: 10.1038/ijo.2009.182
|View full text |Cite
|
Sign up to set email alerts
|

Capsiate administration results in an uncoupling protein-3 downregulation, an enhanced muscle oxidative capacity and a decreased abdominal fat content in vivo

Abstract: Objectives: The involvement of skeletal muscle mitochondrial uncoupling protein-3 (UCP3) in the control of energy expenditure in skeletal muscle and at the whole-body level is still a matter of debate. We previously reported that UCP3 downregulation is linked to an enhanced mitochondrial energy metabolism in rat skeletal muscle as a result of acute capsiate treatment. Here, we aimed at investigating noninvasively the effects of chronic capsiate ingestion on metabolic changes occurring in exercising gastrocnemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 22 publications
3
20
0
1
Order By: Relevance
“…69,70) Capsinoids were also demonstrated to enhance metabolic rate and energy expenditure in WT mice, but not in TRPV1KO mice. In addition, capsiate administration contributes to enhancement of aerobic ATP production and reduction of body fat content, 71) and also up-regulates UCP1 and UCP2 expression. 72,73) Mice given the TRPV1 agonist monoacylglycerol showed increases in UCP1 expression levels in brown adipocytes and suppressed accumulation of visceral fat in mice fed HFD and sucrose.…”
Section: )mentioning
confidence: 99%
“…69,70) Capsinoids were also demonstrated to enhance metabolic rate and energy expenditure in WT mice, but not in TRPV1KO mice. In addition, capsiate administration contributes to enhancement of aerobic ATP production and reduction of body fat content, 71) and also up-regulates UCP1 and UCP2 expression. 72,73) Mice given the TRPV1 agonist monoacylglycerol showed increases in UCP1 expression levels in brown adipocytes and suppressed accumulation of visceral fat in mice fed HFD and sucrose.…”
Section: )mentioning
confidence: 99%
“…13,38,40 Our results are similar to those obtained in a study by Faraut et al in which the administration of capsiate, an ingredient of Capsicum annuum L., resulted in a lower weight gain coupled to a decreased abdominal fat content, as determined by MRI analysis, although the capsiate-treated rats were hyperphagic compared to control animals. 41 Most of the excess energy is stored in the form of triglycerides in adipose tissue, and increased adipose tissue mass arises through hypertrophy and hyperplasia. 42 The current study showed that it was assumed that the administration of green pepper juice decreased the adipose tissue expandability, although not significantly.…”
Section: Discussionmentioning
confidence: 99%
“…Our approach is not without precedent since there have been other reports in the literature demonstrating the feasibility of achieving weight reduction without energy intake reduction [27][28][29][30]. Calculation of the polar surface area of compound 1 revealed that this area is too large for it to cross the blood brain barrier (supplementary table).…”
Section: Page 9 Of 11mentioning
confidence: 99%